2002
DOI: 10.1074/jbc.m200681200
|View full text |Cite
|
Sign up to set email alerts
|

The Myocardium-protective Gly-49 Variant of the β1-Adrenergic Receptor Exhibits Constitutive Activity and Increased Desensitization and Down-regulation

Abstract: The ␤ 1 -adrenergic receptor (␤ 1 AR) is a major mediator of catecholamine effects in human heart. Patients with heart failure who were hetero-or homozygous for the Gly-49 variant of the ␤ 1 AR (Gly-49-␤ 1 AR) showed improved long-term survival as compared with those with the Ser-49 genotype. Here, the functional consequences of this polymorphism were studied in cells expressing either variant. The Gly-49-␤ 1 AR demonstrated characteristic features of constitutively active receptors. In cells expressing the Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
149
1
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(171 citation statements)
references
References 30 publications
10
149
1
9
Order By: Relevance
“…The Ser49Gly polymorphism with a minor allele frequency of 22% has been demonstrated to modulate receptor sensitivity [23]. In clinical studies, variation in the amino acid residue at this location has been shown to influence resting heart rate and survival in a small heart failure cohort [24,25].…”
Section: -Ar Polymorphismsmentioning
confidence: 99%
“…The Ser49Gly polymorphism with a minor allele frequency of 22% has been demonstrated to modulate receptor sensitivity [23]. In clinical studies, variation in the amino acid residue at this location has been shown to influence resting heart rate and survival in a small heart failure cohort [24,25].…”
Section: -Ar Polymorphismsmentioning
confidence: 99%
“…The two subtypes have been directly compared by heterologously expressing each in the same cell line. ␤ 1 AR is more resistant to agonist-mediated downregulation than ␤ 2 AR in CHW (25)(26)(27) and HEK 293 cells (28) and in some studies, undergoes up-regulation in the latter cells (29,30).…”
mentioning
confidence: 99%
“…For example in the human β 1 -adrenoceptor Ser49Gly, a SNP located in the N-terminus, displays a distinct trafficking phenotype (57) with the variant exhibiting increased basal and agoniststimulated adenylyl cyclase activity as well as enhanced agonist-induced downregulation (58). For the β 2 -adrenoceptor the picture is more complex with an Arg16Gly variant receptor displaying enhanced agonist-promoted downregulation whilst a Gln27Glu polymorphism is resistant to degradation (reviewed in (59).…”
Section: The Integrity Of the Pdz-binding Motif Of The P2y 12 R Is Esmentioning
confidence: 99%